2009
DOI: 10.1016/j.mce.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic dichotomy following developmental exposure to perfluorooctanoic acid (PFOA) in female CD-1 mice: Low doses induce elevated serum leptin and insulin, and overweight in mid-life☆

Abstract: a b s t r a c tThe synthetic surfactant, perfluorooctanoic acid (PFOA) is a proven developmental toxicant in mice, causing pregnancy loss, increased neonatal mortality, delayed eye opening, and abnormal mammary gland growth in animals exposed during fetal life. PFOA is found in the sera and tissues of wildlife and humans throughout the world, but is especially high in the sera of children compared to adults. These studies in CD-1 mice aim to determine the latent health effects of PFOA following: (1) an in uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
190
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(207 citation statements)
references
References 43 publications
(48 reference statements)
12
190
3
2
Order By: Relevance
“…In pregnant mice exposure to PFOS resulted in a decrease in natural killer cell activity, specific IgM response, and a decrease in lymphocyte subpopulations (Keil et al 2008) in the offspring. Similar studies of mice have found a reduced spleen weight and affected PPARs after prenatal exposure to PFOA (Abbott et al 2012;Hines et al 2009). In addition, PFOS exposure has been shown to suppress immunity to influenza A in adult mice (Guruge et al 2009).…”
Section: Discussionmentioning
confidence: 52%
“…In pregnant mice exposure to PFOS resulted in a decrease in natural killer cell activity, specific IgM response, and a decrease in lymphocyte subpopulations (Keil et al 2008) in the offspring. Similar studies of mice have found a reduced spleen weight and affected PPARs after prenatal exposure to PFOA (Abbott et al 2012;Hines et al 2009). In addition, PFOS exposure has been shown to suppress immunity to influenza A in adult mice (Guruge et al 2009).…”
Section: Discussionmentioning
confidence: 52%
“…The doses were reported in published literature to affect body weight without having major effects on pup development or survival. The doses of 0.01 and 0.1 mg/kg of PFOA given on GD 1-17 increased body weight observed from age 10-19 weeks and increased serum leptin and serum insulin at age 21-33 weeks in female CD-1 mice, whereas 0.1 mg/kg PFOA gave a nearly significant increase in blood glucose over control (P=0.06) at 20 min post-glucose challenge in 15-16 weeks old mice (Hines et al, 2009 12 although 3 mg/kg was reported to give some developmental effect (ossifications of limbs) (Lau et al, 2006). Higher doses than 3.0 mg/kg PFOA were not used in our experiment, since 5 mg/kg PFOA on GD 1-17 gave significantly increased number of dams with full litter resorptions in CD-1 mice (Lau et al, 2006).…”
Section: Choice Of Doses Of Pfoa and Pfosmentioning
confidence: 87%
“…Discussion PFOA or PFOS did not increase body weight in any of the doses tested (0.01, 0.1 or 3.0 mg/kg bw/day) up to 20 weeks. Exposure of CD-1 mice on GD1-17 to 0.01, 0.1 and 3.0 mg/kg PFOA significantly increased body weight, and 0.01 and 0.1 mg/kg affected serum insulin and leptin levels in female offspring (Hines et al, 2009). Associations between maternal PFOA, but not PFOS, serum concentration and overweight/obesity and waist circumference in their daughters, and with serum insulin and leptin levels, were also reported in a prospective cohort study (Halldorsson et al, 2012).…”
Section: Determination Of Internal Doses Of Pfoa and Pfosmentioning
confidence: 92%
See 2 more Smart Citations